A mussel-inspired double-crosslinked tissue adhesive intended for internal medical use. (15th March 2016) - Fan, Changjiang; Fu, Jiayin; Zhu, Wenzhen; Wang, Dong-An
Graphical abstract: Abstract: It has been a great challenge to develop aldehyde-free tissue adhesives that can function rapidly and controllably on wet internal tissues with fine adhesion strength, sound biocompatibility and degradability. To this end, we have devised a mussel-inspired easy-to-use double-crosslink tissue adhesive (DCTA) comprising a dopamine-conjugated gelatin macromer, a rapid crosslinker (namely, Fe 3+ ), and a long-term acting crosslinker (namely, genipin). As a mussel-inspired gluing macromer, dopamine is grafted onto gelatin backbone via an one-step reaction, the catechol groups of which are capable of performing strong wet adhesion on tissue surfaces. By addition of genipin and Fe 3+, the formation of catechol–Fe 3+ complexation and accompanying spontaneous curing of genipin-primed covalent crosslinking of gluing macromers in one pot endows DCTA with the double-crosslink adhesion mechanism. Namely, the reversible catechol–Fe 3+ crosslinking executes an controllable and instant adhesive curing; while genipin-induced stable covalent crosslinking promises it with long-term effectiveness. This novel DCTA exhibits significantly higher wet tissue adhesion capability than the commercially available fibrin glue when applied on wet porcine skin and cartilage. In addition, this DCTA also demonstrates fine elasticity, sound biodegradability, and biocompatibility when contacting in vitro cultured cells and blood. In vivo biocompatibility and biodegradability are checked and confirmed via trials of subcutaneous implantation in nude mice model. This newly developed DCTA may be a highly promising product as a biological glue for internal medical use including internal tissue adhesion, sealing, and hemostasis. Statement of Significance: There is a great demand for ideal tissue adhesives that can be widely used in gluing wet internal tissues. Here, we have devised a mussel-inspired easy-to-use double-crosslink tissue adhesive (DCTA) that meets the conditions as an ideal tissue adhesive. It is composed of gelatin–dopamine conjugates – a gluing macromer, Fe 3+ – a rapid crosslinker, and genipin – a long-term acting crosslinker. This DCTA is constructed with a novel complexation-covalent double-crosslinking principle in one pot, in which the catechol–Fe 3+ crosslinking executes a controllable and instant adhesive curing, at the same time, genipin-induced covalent crosslinking promises it with long-term effectiveness in physiology conditions. This novel DCTA, with excellent wet tissue adhesion capability, fine elasticity, sound biodegradability, and biocompatibility, is a promising biological glue for internal medical use in surgical operations.